Effectiveness Of Type C Passive Filters In Reducing Harmonic Currents - Lubis, Azmi Rizki; Sutopo, Adi; Affandi, Marwan; Harahap, Muchsin (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This study aims to see how effective the type C passive filter is in reducing harmonic currents generated by the electrodynamometer induction motor trainer. The method used in this study is to model a C-type passive filter and simulate it with computer software. The type C passive filter modeling is designed to reduce harmonics in the thirty-fifth order. From the observation results, it was found that the thirty-fifth order harmonic current was 1.5% while the IEEE 519-2014 standard limits the thirty-fifth order harmonic current to 1.0%, which has exceeded the permitted standard. After the simulation, the type C passive filter successfully reduced the existing harmonics so that the harmonic content was 0.95%. From the results of this simulation, it can be concluded that the type C passive filter successfully reduced the harmonic content in the thirty-fifth order to 36.29%. This harmonic reduction has also been below the maximum value permitted by the IEEE 519 – 2014 standard at the thirty-fifth order so that the passive filter is effective in reducing the thirty-fifth harmonic produced by the electrodynamometer induction motor trainer.